MANAGEMENT OF IRRITABLE BOWEL SYNDROME THROUGH AYURVEDA: A CASE STUDY - *Nirmal Hanumant,; Meena Ram Lakhan,; Kumar Jitender,; Dharmarajan Prasanth,; Bhatted Santoshkumar, (International Journal of Ayurveda and Pharma Research, 2019)
Irritable bowel syndrome (IBS) is a gastrointestinal disorder characterized by altered bowel habits and abdominal pain in the absence of detectable structural abnormalities. The pathogenesis of IBS is poorly understood, although roles for abnormal gut motor and sensory activity, central neural dysfunction, psychological disturbances, stress, and luminal factors have been proposed. About 10-15% of the population is affected at some time but only 10% of these consult their doctor because of symptoms. In Ayurveda, IBS can be correlated to Grahani Roga due to similarity in their clinical presentation. In this case an effort was made to treat a 32 years old male patient having symptoms of Muhurbaddha Muhurshithil (episode of constipated and loose stools), Apakwa Malapravritti (Stool with mucus), Udarshool (abdominal pain). Patient treated with various Panchakarma (five Bio-cleaning Ayurvedic therapies) procedures like Basti (herbal medicated enema), Takra Dhara (pouring Herbal medicated butter milk on head) and oral medications. At the end of 60 days of treatment patient got significant improvement in episode of constipated and loose stools (75%), distension of abdomen (75%), anorexia (100%) and stool with mucus (100%).